218k views
0 votes
Find and simplify.

f(x)=7-x^2

a) f(x+h)-f(x)

b) f(x+h)-f(x)/h​

1 Answer

4 votes

Answer:

a)
f(x+h)-f(x) = h(-h-2x)

b)
( f(x+h)-f(x))/(h)=-h-2x

Explanation:

Our parent function is


f(x)=7-x^2


f(x+h) = 7-(x+h)^2


= 7-(x^2+h^2+2xh)


=7-x^2-h^2-2xh


f(x+h)-f(x)= 7-x^2-h^2-2xh-(7-x^2)


= 7-x^2-h^2-2xh-7+x^2


f(x+h)-f(x) = -h^2-2xh

taking out h as GCF

a)
f(x+h)-f(x) = h(-h-2x)

also

b)
( f(x+h)-f(x))/(h)=(h(-h-2x))/(h)


( f(x+h)-f(x))/(h)=-h-2x

User WestleyArgentum
by
4.9k points